2003
DOI: 10.1007/s00063-003-1230-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatrische Beteiligung des systemischen Lupus erythematodes

Abstract: The treatment of cerebral lupus is empiric, due to a lack of randomized studies. Inflammatory brain lesions are treated with corticosteroids and immunosuppressive drugs (e. g., cyclophosphamide). Anticoagulant therapy with coumarins (at a target INR of 3.0-3.5) is recommended in cases of thrombotic events associated with antiphospholipid antibodies. However, no studies exist on patients with arterial thrombosis, including strokes, supporting this target INR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
(131 reference statements)
0
2
0
1
Order By: Relevance
“…29 European League Against Rheumatism (EULAR) recommendations 17 indicate that therapeutic choices should reflect the nature of the underlying process (ie, inflammatory or thrombotic). It is necessary, therefore, to consider the current hypotheses regarding the underlying mechanisms of NPSLE.…”
Section: Evidentiary Basis Of Treatmentmentioning
confidence: 99%
“…29 European League Against Rheumatism (EULAR) recommendations 17 indicate that therapeutic choices should reflect the nature of the underlying process (ie, inflammatory or thrombotic). It is necessary, therefore, to consider the current hypotheses regarding the underlying mechanisms of NPSLE.…”
Section: Evidentiary Basis Of Treatmentmentioning
confidence: 99%
“…The metanalytic data showed that anti-nucleosome abs have comparable specificity but higher sensitivity than anti-dsDNA abs do for the diagnosis of SLE (19). Cerebrospinal fluid (CSF) pleocytosis was found in 30%, and oligoclonal bands (OCBs) were detected in 25–42% of cases (20). In the cerebral magnetic resonance imaging (cMRI), small focal hyperintensities, mainly subcortical frontoparietal or periventricular, can be detected in 15–60% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Μεταξύ των μελετών ποιοτικής τάξης ΙΙΙ, τρεις τεκμηρίωσαν μια στατιστικά σημαντική συσχέτιση,172,183, 197 και δύο όχι 136,170. Σε μια άλλη μελέτη ποιοτικής τάξης IIb,198 με περιορισμένο όμως αριθμό ασθενών, 28 ασθενείς με ΣΕΛ αξιολογήθηκαν μέσω MRI εγκεφάλου και μέσω υπολογιστικής τομογραφίας εκπομπής ποζιτρονίων (ΡΕΤ) και συγκρίθηκαν με 10 υγιείς εθελοντές. Η κεφαλαλγία η μελέτη δεν επικεντρώθηκε στην κεφαλαλγία ή στην ημικρανία 199.…”
unclassified